2004
DOI: 10.1113/jphysiol.2004.068643
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of neuronal‐ and cardiac‐type sodium channels for murine sinoatrial node pacemaking

Abstract: The majority of Na + channels in the heart are composed of the tetrodotoxin (TTX)-resistant (K D , 2-6 µM) Na v 1.5 isoform; however, recently it has been shown that TTX-sensitive (K D , 1-10 nM) neuronal Na + channel isoforms (Na v 1.1, Na v 1.3 and Na v 1.6) are also present and functionally important in the myocytes of the ventricles and the sinoatrial (SA) node. In the present study, in mouse SA node pacemaker cells, we investigated Na + currents under physiological conditions and the expression of cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
210
2
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(233 citation statements)
references
References 30 publications
20
210
2
1
Order By: Relevance
“…Several lines of evidence have shown that TTX-S channels are localized at t-tubules in ventricular myocytes [21,29] and in sinoatrial node [47,48], although the physiological role of these channels is not well understood [20,49]. We propose that at least a portion of the increased I NaP observed in Scn1b null myocytes may be attributable to one or more TTX-S channels in addition to effects on TTX-R Na v 1.5.…”
Section: Discussionmentioning
confidence: 78%
“…Several lines of evidence have shown that TTX-S channels are localized at t-tubules in ventricular myocytes [21,29] and in sinoatrial node [47,48], although the physiological role of these channels is not well understood [20,49]. We propose that at least a portion of the increased I NaP observed in Scn1b null myocytes may be attributable to one or more TTX-S channels in addition to effects on TTX-R Na v 1.5.…”
Section: Discussionmentioning
confidence: 78%
“…Individual SAN cells were isolated from right atria of the SHR and WKY based on methods described previously 36 with some modifications (see Methods in the online supplement).…”
Section: Single Cell Experimentsmentioning
confidence: 99%
“…Low concentration of TTX, 100-200 nM, inhibited Na v 1.1, while full inhibition of Na v 1.5 required more than 20-30 µM TTX (Antoni et al 1988;Maier et al 2003;Lei et al 2004). These pharmacological treatments could easily separate Na v 1.1 from Na v 1.5.…”
Section: Discussionmentioning
confidence: 99%
“…Several Na + channel isoforms, with Na v 1.5 channel being a main, were confirmed in the cardiac tissue (Haufe et al 2005). However, Na v 1.1, Na v 1.3 and Na v 1.6 that preferentially expressed in neurons are also detected (Maier et al 2003;Lei et al 2004). Previous studies have demonstrated that Na v 1.5 is involved in action potential propagation, but both Na v 1.1 and Na v 1.5 contribute to the pacemaking in SAN (Haufe et al 2005).…”
Section: Introductionmentioning
confidence: 98%